2021
DOI: 10.37341/jkg.v0i0.232
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Public Confidence In Accessing Public Safety Center-119 Services Through First Aid Training

Abstract: Background: Emergency conditions in Indonesia can be caused by the vulnerability of disasters, accidents and diseases that threaten life or cause disability in humans. Emergency conditions require immediate assistance to prevent death and disability. The community as the first helper holds a very important key to the safety of individuals who are experiencing emergency conditions. Not all people are familiar with the PSC-119 service. The results of the preliminary study also showed that most of the respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…This study found an increase in community attitudes in providing assistance to victims of emergency situations. This confirms previous studies found that there was an increase in community confidence in accessing PSC-119 services after first aid training was carried out for victims with significant emergency conditions (Sunarto & Harnanto, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…This study found an increase in community attitudes in providing assistance to victims of emergency situations. This confirms previous studies found that there was an increase in community confidence in accessing PSC-119 services after first aid training was carried out for victims with significant emergency conditions (Sunarto & Harnanto, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Next, psychomotor is related to specific physical and affective abilities, which consist of emotional development including attitudes, behavior, responsibility, emotions, and respect. Moreover, emergency training can also increase the self-confidence of the community in accessing medical emergency services (Sunarto & Harnanto, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the results of previous studies obtained data that integrated first aid training with instructors directly from PSC119 groups can enhance public confidence in accessing PSC 119 services. The first aid training materials provided cover the goals and benefits of first aid for the safety of the victims or survivors the ability to successfully communicate with aid easily self-reliances information when requesting services the importance of the first aid workers role in providing first aid PSC 119 referral services to the community in implementing the SPGDT and requesting first aid procedures if first aid workers find survivors as well as first aid procedures given y lifeguards while waiting for ambulance to arrive (Sunarto & Harnanto, 2021). An algorithm is essential to guide a first aid simulation.…”
Section: Discussionmentioning
confidence: 99%